(untitled) (Third Sector Social Economic Review, 2026)
The study aims to identify the asymmetric effects of climate policy uncertainty on agricultural commodity returns at different time scales. For this purpose, a three-stage procedure was implemented and the causality relationships from asymmetric climate policy uncertainty shocks to positive and negative shocks of 12 agricultural commodity returns were tested with Pata and Yılancı (2020) Fractional Frequency Flexible Fourier Form Toda & Yamamoto causality test. The most important finding of the study is that there are causalities from increases and decreases in the climate policy uncertainty index to the increases and decreases in all agricultural commodity returns. In addition, the study found asymmetric relationships from climate policy uncertainty shocks to all agricultural commodity returns. Another important finding of the study is that there is a causal relationship from asymmetric climate policy uncertainty shocks to increases and decreases in all agricultural commodity returns in the very short run. The results for different time scales show that there are more causal relationships from asymmetric climate policy uncertainty shocks to increases and decreases in agricultural commodity returns in the very short run, long run, medium run and short run, respectively. The findings also show that almost all causal relationships are persistent. The results indicate that climate policy uncertainty is a strategic risk factor not only for environmental sustainability but also for economic stability and food security.